Fibro-Epithelial Hyperplasia Mimicking Mucocele - Jain, K; Singh, BD; Dubey, A; Avinash, A (Kathmandu University Medical Journal, 2015)
The effects of chronic local irritation have been seen commonly in the form of fibroma or mucocele in children. We report a ten year old girl with the chief complaint of swelling in the lower right region of labial mucosa which was diagnosed clinically as mucocele and histologically as fibro-epithelial hyperplasia. Surgical excision was done under local anesthesia with no post-operative complication. Kathmandu University Medical Journal Vol.12(2) 2014: 146-148